Child Labor Across the Developing World : Patterns and Correlations - Fares, Jean; Raju, Dhushyanth (World Bank, Washington, DC, 2012)
The aim of this study is two-fold. First, based on summary data at the country-level for an unusually large set of developing countries originally obtained from household sample surveys conducted between 1993 and 2003, the authors construct a detailed profile of child economic activity and child labor, attempting, wherever the data permit, to identify similarities and differences across regions and between genders. Second, they link the country-level data on child economic activity and child labor to country-level indicators of the state of economic and social development in the same time period in order to (1) ascertain if cross-country correlations previously identified in the literature are found in the data, and (2) illumine other possible correlations that may exist. As part of this exercise, the authors examine one important relationship that has thus far not been directly investigated in the literature, namely, the cross-country correlation between child labor, agriculture, and poverty.